Regional Government Policy in Efforts to Improve the People's Economy an Islamic Perspective (Study of Zapin Dance Tourism in Bengkalis District) - Muhammad Ashsubli; Robithoh Alamhadi; Mohamad Ali Andrias; Sandra Leoni Prakasa Yakub (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study examines regional government policies in the development of Zapin Dance tourism as an effort to improve the community’s economy in Bengkalis Regency from an Islamic perspective. The research was motivated by the underutilization of cultural tourism potential in Bengkalis despite the existence of Zapin Dance as a representation of Malay-Islamic cultural identity with economic and social value. This study aimed to analyze government strategies, community participation, economic contributions, and challenges associated with the development of Zapin Dance tourism. A qualitative approach with a descriptive case study design was employed. Data were collected through semi-structured interviews, observations, and documentation involving government officials, cultural leaders, tourism activists, local business actors, and community representatives in Bengkalis Regency. The data were analyzed using thematic analysis through coding, categorization, and theme development processes. The findings revealed that the regional government has implemented several tourism development initiatives through cultural festivals, financial assistance, tourism promotion, and collaboration with cultural communities. Community participation also plays a significant role in preserving Zapin Dance traditions and supporting local tourism activities. Furthermore, Zapin Dance tourism contributes to local economic activities through small businesses, traditional handicrafts, culinary services, and tourism-related informal sectors. However, several obstacles remain, including limited funding, inadequate infrastructure, weak digital promotion, and declining youth participation in cultural preservation. From an Islamic perspective, the development of Zapin Dance tourism reflects the principle of maslahat because it supports social welfare, cultural sustainability, and the preservation of Malay-Islamic values. Therefore, stronger collaboration between government institutions, cultural communities, and tourism stakeholders is necessary to optimize the sustainability and competitiveness of Zapin Dance tourism in Bengkalis Regency.